Electromagnetically Induced Transparency Analogue by Self‐Complementary Terahertz Meta‐Atom. Issue 4 (19th January 2016) - Jung, Hyunseung; In, Chihun; Choi, Hyunyong; Lee, Hojin
Abstract : In the past years, many researchers have tried to realize the electromagnetically induced transparency (EIT) phenomena from the metamaterial arrays for the attractable applications such as slow light devices, novel optical communication systems, and nonlinear optical devices. Most of metamaterial enabled EIT analogues reported so far are based on the destructive interference between the bright and dark meta‐atoms. Whether they are located on the same plane or off the plane, EIT‐like properties can be achieved only by breaking the symmetry between the bright and dark meta‐atoms. In this study, a novel self‐complimentary terahertz meta‐atom is developed by combining cut‐wire resonators and its pseudo‐complimentary pattern within a single meta‐atom. From the measurement results, it is verified that the proposed meta‐atom can exhibit EIT‐like phenomenon within a single unit cell by controlling the focus of the electric field induced by the incident terahertz waves within the self‐complimentary meta‐atom cell as predicted by the numerical simulation as well as by the theoretical forced oscillation model. Abstract : A novel metamaterial with an electromagnetically induced transparency phenomenon is developed by a self‐complementary terahertz meta‐atom. It is verified experimentally that the proposed meta‐atom can exhibit electromagnetically induced transparency within a unit cell by controlling the focus of the electric field induced by the incident terahertz waves within the cell, as predicted by numerical simulations and a theoretical forced oscillation model.